Respuesta del hibrido de maíz (Zea mays L.) DK-7088 a varias fuentes y niveles de fertilización mineral en la zona de Valencia. - Benalcázar Chalen, Erik Lenin (2010)
This research was conducted during the winter of 2010 on the grounds of the "El Chaparral # 2" Mr. José Luis Rosales located in the km 16 road-Valencia Quevedo, Los Rios province, between geographical coordinates 01 º 06 '2 "South Latitude and 79 º 29' 28" west longitude, at an altitude of 120 meters. The local climate is tropical moist forest type, characterized by an average annual temperature of 24.9 º C, annual rainfall of 2286.6 mm, relative humidity 84%. And 896 hours of annual average heliophany. The soil is clay loam, irregular topography and drainage and pH of 5.8-6.0. Raised the overall objective: To evaluate the response of maize hybrid DK7088 to various sources and levels of mineral fertilizer in the area of Valencia. And the specific objectives: to determine how the response of maize depends on the source and alternative fertilization Know the difference between the response of maize to different combinations of sources and levels of fertilization to the traditional methods using nitrogen fertilization producer, Analysis of production and profitability of corn hybrid DK-7088 to the source and levels of fertilization. Subject to the hypothesis: The development of the productive potential of hybrid DK-7088 depends on the best combinations of sources and levels of fertilization. For comparison of treatment means was used Duncan's test at 0.05% chance. The variables were days of flowering, diseased ears, cobs harvested, mole weight and grain moisture showed no significant differences. The highest plant height 2.46 m the treatment record five individual (250 de EQ2+250 de AGROFEED+0 AMIDAS+200 de NITROMAG).The four treatment (250 Kg de EQ2 + 250 Kg de AGROFEED MAIZ DESARROLLO + 0 Kg AMIDAS + 250 Kg de NITROMAG) had the highest ear insertion height. With larger and thicker it had four treatments ( 250 Kg de EQ2 + 250 Kg de AGROFEED MAIZ DESARROLLO + 0 Kg AMIDAS + 250 Kg de NITROMAG) to 16.79 cm and the treatment six (250 Kg de EQ2 + 250 Kg de AGROFEED MAIZ DESARROLLO + 60 Kg AMIDAS + 150 Kg de NITROMAG) with 4.86 cm. El greater total grain weight and ear the three treatment (200 Kg de EQ2 + 200 Kg de AGROFEED MAIZ DESARROLLO + 50 Kg AMIDAS + 100 Kg de NITROMAG) record with 7.91 kg and 9.29 kg more than control. The highest yield kg / ha was obtained by treatment three (200 Kg de EQ2 + 200 Kg de AGROFEED MAIZ DESARROLLO + 50 Kg AMIDAS + 100 Kg de NITROMAG) 11084.33 originated with considerable economic profits and in turn achieved a good return for producers in the area.